Field problems of beans in Latin America - Schwartz, Howard F.; Gálvez E., Guillermo E.; Schoonhoven, Aart van; Howeler, Reinhardt H.; Graham, Peter H.; Flor Montoya, Carlos A. (International Center for Tropical Agriculture, 1978)
A description is given of the different factors limiting to bean production in Latin America, type of damage caused, environmental conditions where they prevail, and possible control measures. With regard to diseases, the following are discussed: aphid-, whitefly- and beetle-transmitted viruses, foliage- and pod- infecting fungi, root- and stem-infecting fungi, bacterial diseases, nematodes and seed pathology. Insect pests are grouped according to the part of the plant attacked: seedlings, leaves, pods and the stored seeds. Nutritional disorders include aspects of mineral toxicity and deficiency, Miscellaneous problems include chemical damage, environmental factors and genetic abnormalities. All these problems are illustrated with color photos to make identification easier. (CIAT)